Preventative Strategies to Curb School Violence: A Case Study of Selected Schools in Hhohho District of Eswatini, Mbabane - Nomathemba Nomakhosi Sibisi; Nonhle Tracey Sibisi; Zandile Faith Mpofu (Social Sciences, 2024)
The violence occurring in schools is a concerning phenomenon with pervasive implications for learners, teachers, and communities. Its impact culminates in fear, stress, and a reduced sense of safety among learners and teachers. Its consequences extend beyond physical harm, thus affecting an individual’s mental well-being. This study provides a precis of the comprehensive nature of school violence and preventative strategies meant to curb this phenomenon. This study employed a case study design located within the interpretative paradigm. A qualitative approach was used to delve into the perceptions of learners and educators on the nature of school violence and measures that could be adopted to prevent it. Thirty (n = 30) participants involving ten learners (n = 10), ten parents (n = 10), and ten educators (n = 10) were purposively sampled. Ten learners participated in focus-group discussions, with five learners representing each school located in Mbabane, Eswatini (Imbabane Central and Mater Dolorosa High Schools). Semi-structured interviews were conducted with 10 teachers and 10 parents (5 parents and 5 teachers from each school). A lack of effective methods of disciplining learners was identified as a cause of bullying and aggressive behaviours among learners. The findings reflect that violence is deeply rooted in harmful social norms, with corporal punishment being widely advocated by the participants. The findings indicate a crucial need for adopting an integrated and collaborative approach to the development and implementation of effective preventative measures.